Agile Methods on the Shop Floor: Towards a "Tesla Production System"? - Timo Daum (Weizenbaum Institute for the Networked Society - The German Internet Institut, 2022)
This discussion paper investigates two questions: To what extend can Tesla be regarded as a digital firm, and do we - as a result - see elements of a distinct "Tesla production system"? While the EV-startup is widely approached as a competing automaker focusing on the electric drive train, which it certainly is, this paper argues that it can only fully be understood as a digital firm - a digital car company with a digital product embedded in a digital ecosystem. Its roots in Silicon Valley, its software-first approach, and its strategic exploitation of user activity data point into this direction. In the second part, this paper explores to what extent Tesla's rootedness in software and its Silicon-Valley ancestry gave reason to introduce methods borrowed from software development on the shop floor. To a certain degree, concepts from agile software development found their way to the very assembly-line at Tesla. Although it might be exaggerated to speak of a distinct "Tesla Production system", indications for a considerable and possibly enduring alteration of Lean Production paradigm can be determined.
Additional information: This work has been funded by the Federal Ministry of Education and Research of Germany (BMBF) (grant no.: 16DII121, 16DII122, 16DII123, 16DII124, 16DII125, 16DII126, 16DII127, 16DII128 - "Deutsches Internet-Institut") and the Federal Ministry of Labour and Social Affairs of Germany (BMAS).
Keywords: 650; Elektrofahrzeug; Produktion; Digitalisierung; Software; Fertigung